Robustness of the hypoxic response: Another job for miRNAs? - de Lella Ezcurra, Ana Laura (2012)
Living organisms are constantly exposed to environmental and genetic perturbations. Biological robustness enables these organisms to maintain their functional stability in the presence of external or internal changes. It has been proposed that microRNAs (miRNAs), small non-coding regulatory RNAs, contribute to robustness of gene regulatory networks. The hypoxic response is a major and well-characterized example of a cellular and systemic response to environmental stress that needs to be robust. miRNAs regulate the response to hypoxia, both at the level of the main transcription factor that mediates this response, the hypoxia-inducible factor (HIF), and at the level of one of the most important systemic outcomes of the response: angiogenesis. In this review, we will take the hypoxic response as a paradigm of miRNAs participating in circuits that provide robustness to biological responses.